(untitled) (Annual of the Faculty of Philosophy in Skopje, 2024)
The text is a plausible presentation and critical review of the main work of Theodosius Dobzhansky: “Evolution of Humanity”. It tries to show and proves that Dobzhansky tries and largely succeeds in offering a different, let’s say, dialectical interpretation of the biological evolution of humanity, i.e., the stages and differences in the evolution of the human species and race. Following in the footsteps of, but also in contrast to, traditional Darwinism and some similar evolutionary theories, Dobzhansky insists on the claim that evolution, primarily biological, is not over, but that it is still going on, despite human, i.e., a cultural intervention, namely simultaneous and together/ conjunctive with it, which seeks to influence and change the directions of the existing natural flows and processes. During the multi-millennium history, biology and culture became interdependent and interfering, with which man (woman and man) with his appearance asserted himself as the main and most responsible factor/agent of the fate of the human race and the survival of the human community/human species, namely survival of oneself, but also of the totality and entirety of the planetary biodiversity, as a necessary prerequisite for one’s own survival and existence. In his research on the evolution of humanity, Dobzhansky starts from the inspiring views of some famous predecessors, such as Pierre Teilhard De Chardin, but we can argue that Dobzhansky influenced many of his contemporaries, including Noam Chomsky, especially when it comes to linguistic research on the genesis and emergence of human language, and the influence of transformative-generative grammar on the development of the human mind, i.e., on the development of the human brain. At the same time, we can state that Dobzhansky’s research and insights correspond and coincide with the research and ethical attitudes of some modern bioethicists, philosophers of biology and culturologists, as well as with the attitudes of many like-minded people and followers.